ANALISIS PENGARUH KUALITAS LAYANAN DAN PERSEPSI HARGA TERHADAP MINAT BELI MELALUI REPUTASI DANWORD OF MOUTH (Studi Pada Maskapai Berbiaya Rendah di Indonesia) - Oktav, Riyandika; Sukresna, I Made (Faculty of Economics and Business Diponegoro University, 2018)
Based on the facts there is a decline in the market share and the increasing complaints of low-cost carrier users in Indonesia. This study aims to analyze the effect of service quality and price perception on purchase intention made to low-cost carrier users in Indonesia. The variables used in this study are service quality, and price perception as independent variables, then reputation and word of mouth as the last intervening variable ppurchase intention as the dependent variable. According to Chiu, et al (2015) it is necessary to improve the quality of flight services to meet consumer needs and expectations to increase purchase intention. Meanwhile, according to Liu and Lee (2016) not only through improving the quality of services that can increase the interest of low-cost carrier users, but also must provide price perceptionto consumers.The sample in this study were 180 respondents, namely low-cost carrier users in Indonesia. The method used was purposive sampling by distributing questionnaires to low-cost carrier users in Indonesia. Data analysis used in this study is structural equation model (SEM).Based on the results of SEM data processing shows that all hypotheses tested have a positive and significant influence. Based on the total effect, obtained the best path is service quality â†’ reputation â†’ purchase intention.